The Intelligibility of Indonesian Learners of English (ILE) in Understanding the Pronunciation of English Spoken by Thai Students - Destiyana Destiyana; Malikatul Laila (Universitas Cokroaminoto Palopo, 2020)
This study carried out an intelligibility of English pronunciation by Thai students. The objectives are to explain the intelligibility of ILE in the pronunciation of English and to identify the typical kind of English sounds which are delivered by the students in Thailand. The data included Thai English words gathered by using participant observation. The result showed: (1) the level of intelligibility of ILE have perceived intelligible (50.6%) and their unperceived as much as 49.4% in the English sounds pronunciation by ThaiE, (2) the typical kind of English sounds produced by ThaiE can be seen from the pronunciation of consonant sounds, vowels and diphthong sounds. For example, the vowel sounds (a, ׀, i ə, Λ, a, ɑ, ɒ, o, U, u) are typically sounded by ThaiE’s pronunciation is understood well and intelligible by Indonesian Leaners of English (ILE).